SYNTHESIS AND STRUCTURAL ANALYSIS OF NICKEL FERRITE SYNTHESIZED BY CO-PRECIPITATION METHOD - Durgadsimi, S.U.; Kattimani, V.R.; Maruti, N.S.; Kulkarni, A.B.; Mathad, S.N. (KU Publ., 2021)
The Nickel ferrite has been synthesized by co-precipitation method. X-ray diffraction pattern confirms the formation of cubic spinel structure with lattice constant 8.347Å. Structural properties like X-ray density, average crystalline size, bond length, dislocation density and microstrain have been studied. The scanning electron microscope images show grain of bead structures. The Fourier transform infrared spectroscopy spectrum of nickel ferrite under investigation reveals the formation of a cubic spinel structure showing two significant absorption bands, corresponding to high frequency band ν1and low frequency band ν2arising from tetrahedral (A) and octahedral (B) interstitial sites respectively.
Keywords: Nickel ferrite; X-ray diffraction pattern; scanning electron microscope; Fourier transform infrared spectroscopy